Function analysis of LIPI-4 in Listeria monocytogenes reveals a key role of flagella formation in the regulation of virulence - Caixia Liu; Xun Ma; Bin Jia; Ruixuan Qian; Shengjie Gao; Lu Liu; Yatao Qi; Zhongke Yin; Guangdong Hu; Jing Wang (Virulence)
Listeria pathogenicity island 4 (LIPI-4), a newly discovered virulence gene cluster, plays a critical role in the development of central nervous system infections and maternal-fetal infections caused by Listeria monocytogenes. This study aimed to clarify the pathogenic role of LIPI-4 in L. monocytogenes. Our findings revealed that LIPI-4 is involved in the invasion and intracellular proliferation of L. monocytogenes in Caco-2, hCMEC/D3, HTR-8/Svneo, and RAW264.7 cells and facilitates its intercellular migration. Further investigations demonstrated that the deletion of LIPI-4 significantly reduces bacterial motility and impairs flagellum formation. Transcriptomic analysis further indicated that LIPI-4 regulates flagellum formation by modulating microbial metabolic processes and carbon metabolism. Our research demonstrates that LIPI-4 promotes flagellum formation through metabolic regulation, thereby enhancing L. monocytogenes colonization and cellular invasion. This discovery provides novel insights into the pathogenic mechanisms of L. monocytogenes.